Trypanosoma cruzi: Entry into Mammalian Host Cells and Parasitophorous Vacuole Formation - Barrias, Emile S.; Carvalho, Tecia M.; De Souza, Wanderley (Frontiers in Immunology, 2013)
Trypanosoma cruzi, the causative agent of Chagas disease, is transmitted to vertebrate hosts by blood-sucking insects. This protozoan is an obligate intracellular parasite. The infective forms of the parasite are the metacyclic trypomastigotes, amastigotes and bloodstream trypomastigotes. The recognition between the parasite and mammalian host cell, involves numerous molecules present in both cell types, and similar to several intracellular pathogens, T.cruzi is internalized by host cells via multiple endocytic pathways. Morphological studies demonstrated that after the interaction of the infective forms of T.cruzi with phagocytic or non-phagocytic cell types, plasma membrane protrusions can form, showing similarity with those observed during canonical phagocytosis or macropinocytic events. Additionally, several molecules known to be molecular markers of membrane rafts, macropinocytosis and phagocytosis have been demonstrated to be present at the invasion site. These events may or may not depend on the host cell lysosomes and cytoskeleton. In addition, after penetration, components of the host endosomal-lysosomal system, such as early endosomes, late endosomes and lysosomes, participate in the formation of the nascent parasithophorous vacuole (VP). Dynamin, a molecule involved in vesicle formation, has been shown to be involved in the parasitophorous vacuole release from the host cell plasma membrane. This review focuses on the multiple pathways that T.cruzi can use to enter the host cells until complete VP formation. We will describe different endocytic processes, such as phagocytosis, macropinocytosis, endocytosis using membrane microdomains and clathrin-dependent endocytosis and show results that are consistent with their use by this smart parasite. We will also discuss other mechanisms that have been described, such as active penetration and the process that takes advantage of cell membrane wound repair.